Managing missionary identity in the digital age: How missionaries utilize digital media among multiple social groups. Issue 2 (April 2018) - Nehrbass, Kenneth
The way that missionaries manage their identities has changed significantly since the days they mailed out several printed newsletters a year to a small audience "back home." The space for this negotiation of identity has moved from private to public; and the interlocutors who access these blogs, emails, and posts are no longer homogenous. This original research study uses quantitative and qualitative methods to understand how missionaries avow the multiple layers of their identities in the digital age. I conclude that missionary updates are encoded along indexical "cultural scripts" that can be decoded idiosyncratically by various audiences.